Helmut Rennert’s universal genesis of endogenous psychoses: the historical concept and its significance for today’s discussion on unitary psychosis - Kumbier, Ekkehardt; Herpertz, Sabine (Psychopathology, 2010)
Next to Karl Leonhard (1904-1988), Helmut Rennert (1920-1994) was the internationally best known representative of psychiatry from the former German Democratic Republic (GDR). He rose to prominence above all through his model of the universal genesis of endogenous psychoses, which constituted an antithesis to Leonhard’s differentiated division. The ‘polar opposite’ aspects of Rennert and Leonhard are represented with an emphasis on their contrasting views of psychiatric nosology. In this respect, Rennert’s model conceptions constitute the primary focus of attention. The fact that both concepts continue to possess topical perspectives to this day is reflected in the current discussion regarding nosological, categorical, syndromatological and dimensional approaches in relation to the further development of the classification systems of mental disorders. The preparatory work on the future classification systems will potentially omit the dichotomy between schizophrenic and affective disorders. These endeavors are in accordance with Rennert’s unitarian psychopathological view and support his acceptance of the psychopathological continuity from affective to schizophrenic syndromes. The current discussion concerning the future classification is in line with Rennert, whose aim was to provide an unconventional model that unites findings from the different fields of psychiatric research. The classification of mental disorders without a previous establishment on the basis of fundamental theoretical assumptions could certainly foster a dynamic development in the future. A differentiated knowledge of the history of the ideas of unitary psychosis and their further development might be helpful in this development and can be of particular use when critically questioning explanatory approaches that are prone to simplification.